The effect of accounting profit information on stock prices in food and beverage companies on the Indonesian stock exchange - Cici Sutarmi (IHSA Institute, 2023)
So far, financial reports, especially balance sheets and profit and loss are still believed to be reliable tools for users to reduce the risk of uncertainty in making economic decisions. In this study, the authors use accounting profit information which is focused on the three profit figures, namely gross profit, operating profit, and net profit based on the profit and loss financial statements. The purpose of this study was to determine the effect of accounting profit information on stock prices in food and beverage companies listed on the IDX in 2007-2011. Information and data in this study include secondary data. Secondary data was obtained from the company's financial reports and annual reports through the Makassar representative Capital Market Information Center (PIPM), company official website and IDX official website. The research sample is a food and beverage company in the period 2007-2011. The number of samples used is 10 companies. Hypothesis testing uses multiple regression analysis with the help of SPSS version 19.0. Using the t test to analyze the closeness of the relationship of individual variables, and the F test to see the relationship simultaneously. The test results failed to prove the effect of gross profit and operating profit on stock prices in food and beverage companies on the IDX in 2007-2011. Net income is the only variable that has a positive and significant effect on stock prices in food and beverage companies on the IDX in 2007-2011. Hypothesis testing uses multiple regression analysis with the help of SPSS version 19.0. Using the t test to analyze the closeness of the relationship of individual variables, and the F test to see the relationship simultaneously. The test results failed to prove the effect of gross profit and operating profit on stock prices in food and beverage companies on the IDX in 2007-2011. Net income is the only variable that has a positive and significant effect on stock prices in food and beverage companies on the IDX in 2007-2011. Hypothesis testing uses multiple regression analysis with the help of SPSS version 19.0.